GENETIC MANIPULATION OF TOMATO PLANT WITH ANNEXIN GENE THROUGH AGROBACTERIUM MEDIATED TRANSFORMATION - SATYA PRAKASH MISHRA; SHREEDHAR G. BHAT; SANJAY SINGH (The Bioscan, 2010)
The present study of genetic manipulation by incorporation of annexin gene has been attempted in tomato plant, Lycopercicum esculantum through Agrobacterium tumefaciens. The annexin gene construct was transferred into plant Genomic DNA by using leaf disc preparation, co-cultivation and selection media transfer. The selection media consists of kanamycin, augmentin and cefatoxime. Leaf disc containing gene construct survives on selection media and were allow growing in calli, indicating the presence of gene of interest, which was further confirmed by extraction of genomic DNA and PCR analysis. Study revealed that Agrobacterium-mediated transformation in tomato was a successful method for transfer of annexin gene. The methodologies may be used for the commercial production of transformed tomato with salt and drought tolerance.